Computational Fluid Dynamics and Experimental Analysis of a Wind Turbine Blade’s Frontal Section with and without Arrays of Dimpled Structures - Aziz, Shahid; Khan, Abdullah; Shah, Imran; Khan, Tariq Amin; Ali, Yasir; Sohail, Muhammad Umer; Rashid, Badar; Jung, Dong Won (Energies (Basel), 2022)
Horizontal axis wind turbines are used for energy generation at domestic as well as industrial levels. In the wind turbines, a reduction in drag force and an increase in lift force are desired to increase the energy efficiency. In this research work, computational fluid dynamics (CFD) analysis has been performed on a turbine blade’s frontal section with an NACA S814 profile. The drag force has been reduced by introducing an array of dimpled structures at the blade surface. The dimpled structures generate a turbulent boundary layer flow on its surface that reduces the drag force and modifies the lift force because it has greater momentum than the laminar flow. The simulation results are verified by the experimental results performed in a wind tunnel and are in close harmony with the simulated results. For accurate results, CFD is performed on the blade’s frontal section at the angle of attack (AOA) with a domain of 0° to 80° and at multiple Reynolds numbers. The local attributes, lift force, drag force and pressure coefficient are numerically computed by using the three models on Ansys fluent: the Spalart-Allmaras, the k-epsilon (RNG) and the k-omega shear stress transport (SST).